A comparison of atenolol and nebivolol in isolated systolic hypertension - Dhakam, Zahid; Yasmin; McEniery, Carmel M; Burton, Tim; Brown, Morris J; Wilkinson, Ian B (Journal of hypertension, 2008)
Some beta-blockers are less effective in reducing central blood pressure than other antihypertensive drugs, which may explain the higher rate of events in subjects randomized to atenolol in recent trials. We hypothesized that nebivolol, a mixed beta-blocker/nitro-vasodilator, would be more effective than atenolol in reducing central blood pressure and augmentation index (AIx). The aim of the present study was to test this in a double-blind, randomized, cross-over study, in a cohort of subjects with isolated systolic hypertension. Following a 2-week placebo run-in, 16 never-treated hypertensive subjects received atenolol (50 mg), nebivolol (5 mg) and placebo, each for 5 weeks, in a random order. Seated brachial blood pressure and heart rate were measured. Aortic blood pressure, AIx and pulse wave velocity (PWV) were assessed non-invasively. The placebo-corrected fall in brachial pressure was similar between nebivolol and atenolol, as was the reduction in PWV (mean change +/- SEM: -1.0 +/- 0.3 and -1.2 +/- 0.2 m/s; P = 0.2). However, there was less reduction in heart rate (-19 +/- 2 versus -23 +/- 2 beats/min; P < 0.01) and increase in AIx (+6 +/- 1 versus +10 +/- 1%; P = 0.04), following nebivolol. Aortic pulse pressure was significantly lower (50 +/- 2 versus 54 +/- 2 mmHg; P = 0.02) after nebivolol. N-terminal pro-B-type natriuretic peptide (proBNP) rose on both drugs (100 +/- 33 versus 75 +/- 80 pg/ml; P < 0.01 for both, NS for comparison). Nebivolol and atenolol have similar effects on brachial blood pressure and aortic stiffness. However, nebivolol reduces aortic pulse pressure more than atenolol, which may be related to a less pronounced rise in AIx and bradycardia. Whether this will translate into differences in clinical outcome requires further investigation.